Exact Solution of Modified Veselov–Novikov Equation and Some Applications in the Game Theory - Damir Kurmanbayev (International Journal of Mathematics and Mathematical Sciences)
A method of finding exact solutions of the modified Veselov–Novikov (mVN) equation is constructed by Moutard transformations, and a geometric interpretation of these transformations is obtained. An exact solution of the mVN equation is found on the example of a higher order Enneper surface, and given transformations are applied in the game theory via Kazakh proverbs in terms of trees.